إجراءات التقاضي عن بعد في التشريع الجزائري - حفيظ حليمة, حليمة; بالخير, فيروز (My University, 2023)
يعد التقاضي الإلكتروني مصطلح حديث ففي التشريع الجزائري ورد ذكره في 01 افريل 2015 في المادة اربعة من القانون 15/03 ولم يذكر المشرع الجزائري مصطلح التقاضي الإلكتروني بل استعمل عبارة المحادثة المرئية عن بعد وتعني كل جهاز ينقل الصوت والصورة بواسطة موجات الإتصال وأهم ما ميز هذا التقاضي على التقاضي العادي هو سرعة تفيدجراءته بالإضافة الى التوقيع الإلكتروني وهو تنظيم تقني معلوماتي يتيح للخصوم تسجيل دعواهم وتقديم أدلتهم وحضور جلسات المحاكمة تمهيدا للوصول إلى الحكم وتنفيذه دون الحضور الشخصي تتم مكان المحادثة المرئية بمقر المحكمة الأقرب من مكان إقامة الشخص المطلوب وبحضور وكيل الجمهورية المختص إقليميا وأمين الضبط وهذا مانصت عليه المادة 16 من قانون عصرنة العدالة تتمثل إجراءات تسجيل الدعوة الإلكترونية في المواد الجزائية في مثول المتهم من خلال شاشة معروضة في قاعة الجلسات تقابلها شاشة أخرى في المؤسسة العقابية يقوم القاضي بالمناداة على المتهم ويتم استجوابه صوتا وصورة بنفس إجراءات الاستجواب العادية ويحتفظ بتصريحات الجلسة في دعامة إلكترونية ترفق بالملف وتمر الدعوى المدنية بإرسال عريضة عن طريق البريد الإلكتروني أو الرقم السري للمحامي وشروطه العامة لا تختلف عن الشروط المطلوبة في الدعوى العادية ولتحسين التقاضي الإلكتروني فذلك من خلال نشر الوعي القانوني للمحاكم الإلكترونية لدى المواطنين وفي القطاع ووضع عقوبات لمن يتلاعب بالإرسالالإلكتروني والأهم اصدار قانون خاص ينظم المجال الإجرائي والعمل الإداري للمحاكمة عن بعد.Electronic litigation is a modern term. In Algerian legislation, it was mentioned on April 01, 2015 in Article 4 of Law 03/15. The Algerian legislator did not mention the term electronic litigation, but rather used the term video chat at a distance, meaning every device that transmits sound and image by means of communication waves, and the most important thing that distinguishes this litigation In ordinary litigation, it is the speedy implementation of its procedures in addition to the electronic signature, which is an information technology organization that allows the litigants to register their case, present their evidence, and attend the trial sessions in preparation for reaching and implementing the ruling without personal attendance. settings This is what is stipulated in Article 16 of the Law on Modernizing Justice. The procedures for registering the electronic invitation in the penal articles are represented in the appearance of the accused through a screen displayed in the courtroom. It is matched by another screen in the penal institution. The judge calls the accused and he is interrogated Audio and image with the same regular interrogation procedures, and the session statements are kept in an electronic support that is attached to the file. The civil lawsuit passes by sending a petition via e-mail or the lawyer’s password, and its general conditions do not differ from the conditions required in the regular lawsuit. To improve electronic litigation, this is done by spreading the legal awareness of electronic courts among citizens. And in the sector, setting penalties for those who manipulate electronic transmission, and most importantly, issuing a special law regulating the procedural field and administrative work for remote trial
مذكرة ماستر
Keywords: التقاضي الالكتروني، الأنترانت، المحادثة المرئية، التطبيقات الالكترونية , الدعوى الالكترونية; Electronic litigation, the internet, video chat, electronic application, electronic lawsuit.